Neonicotinoids for crop protection: environmental aspects of use - Tsurkan, O.; Panchenko, T.; Chervyakova, L. (Quarantine and plant protection, 2025)
Goal. Ecological assessment of neonicotinoids (imidacloprid, clothianidin, thiamethoxam) for seed treatment. Methods. The study was conducted in accordance with the conditions of the vegetation method. Soybean seeds (Glycine max (L.) Merr.) were treated with insecticides at the rate recommended by the manufacturers. The content of active substances was determined using chromatographic methods of analysis. Statistical processing of the obtained data was carried out using methods of variance and regression analysis. Results. The distribution patterns of active substances in plants and soil are determined by a complex of factors: physicochemical properties (based on the hydrophobicity coefficient log Kow, water solubility, etc.), plant characteristics, cultivation conditions, soil type, and their content during the growing season depends on the rate of application and the initial amount (initial toxic potential) of the pesticide. Detoxification of neonicotinoids occurs according to an exponential model described by the corresponding equations, which can be used to estimate the content of the compound (C, mg/kg) at any remote point in time (t, day), and which are useful for their initial screening in agrocenosis objects. The reduction of neonicotinoids content occurs at different rates (k): 0.049—0.109 days–1 (for plants) and 0.089—0.100 days–1 (for soil). Calculated using a mathematical modeling method, which involves the computational reproduction of detoxification processes based on actual data, T50/T95 are 6.4—14.1 days/27.4—61.0 days (for plants) and 6.9—7.7 days/29.9—33.2 days (for soil), respectively. Conclusions. With regulated use of neonicotinoid-based products for seed treatment, the active ingredients break down in agrocenoses during the growing season to levels that do not exceed hygienic standards and do not pollute the environment.